Legal aspects of e-commerce cooperation between Eurasian economic union and Vietnam - Ablameyko, Maria; Dao, Van Tuyet (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
The paper analyses E-commerce cooperation between Eurasian Economic Union and Vietnam. Economic results or trade between EAEU and Vietnam are analyzed. Main documents and trade aspects between EAEU countries and Vietnam are shown. The legal business actions and responsibility that should be developed are shown. Proposals to develop legislation for further e-commerce extension are given. Special attention should be paid to rapidly growing Artificial Intelligence systems and their regulation at our joint market.